Social stratification, materialism, post-materialism and consumption values: An empirical study of a Chinese sample. Issue 4 (12th September 2016) - Wang, Ying
Abstract : Purpose: The increased income and modernity have greatly impacted Chinese consumers' attitudes and purchasing behavior, making them more sophisticated than ever before. The purpose of this paper is to examine the interrelationship among social stratification, materialism, post-materialism, and consumption values contributing uniquely to understanding Chinese consumers in the context of drastic economic and social changes. Design/methodology/approach: Survey method was used to test the proposed model and answer the research questions. The data were collected in Shanghai, the largest city on the eastern coast of China. A multi-stage random sampling strategy was employed to acquire a representative sample of the population in the city. A total of 2, 910 completed questionnaires were used for data analysis. Findings: The results show that objective social status has a negative effect on post-materialism, whereas subjective social status has a positive effect. Social status does not seem to have a significant effect on materialism. Post-materialism also has a strong positive effect on the consumption orientations of emotional value and social value. Practical implications: China was chosen as the research context in this study. As a booming emerging market, China provides an intriguing platform to examine social stratification and materialism. At the macro level, China is developing a new social structure due to the drastic social and economic changes. At the individual consumer level, as China moves further into a market-oriented economy, traditional Chinese values have changed rapidly. Western consumption values and phenomena such as overspending and conspicuous consumption have begun to take hold in China, especially among young people. It is critical for business managers to understand the shift of consumption values among Chinese in order to successfully capture this market. Originality/value: A cursory review of past literature reveals that researchers have examined materialism primarily along two avenues: one puts materialism within a macro framework involving political interest or civic engagement (e.g. Davis et al., 1999; Inglehart, 1990); the other one takes a micro perspective exploring the impact of materialism on consumer attitudes and behavior (e.g. Park and Rabolt, 2009; Xiao and Kim, 2009). However, little research has been conducted linking the two approaches. The present study intends to examine the interrelationship among social stratification, materialism, post-materialism, and consumption values. Hopefully, it will shed some light on the connection between macro environment and micro consumer behavior. Furthermore, the current research provides evidences for the emerging transformation to a post-materialistic marketplace.